Study of organic honey from the Northeast of Portugal - Gomes, Teresa (2011)
Concerns about traces of numerous toxic substances and authenticity have prompted consumer demand for honey that is certified as organic, based on strict ecological, natural principles and traceability. The present study aims to characterize organic honey samples (n = 73) from Northeast Portugal, with respect to floral nectar origin, physicochemical parameters and microbial safety. The phenols and flavonoids contents, often referred to as responsible for honey’s bioactive properties, were also assessed. All organic honey samples were classified as monofloral lavender (Lavandula sp.), exceeded in quality the international physicochemical standards and showed low microbiological counts (yeast, moulds and aerobic mesophiles), with negative results in respect to fecal coliforms, Salmonella and sulphite-reducing Clostridium spp. Correlation of the palynological, physicochemical and microbiological results is necessary to check the authenticity, quality and sanitation of honey. Although not required by international legislation, results of those assessments provide a complete outlook and elucidation of the organic honey’s properties, which could promote its valorisation.